The Role of miRNA-7 in the Biology of Cancer and Modulation of Drug Resistance - Ewa Gajda; Małgorzata Grzanka; Marlena Godlewska; Damian Gawel (MDPI AG, 2021)
MicroRNAs (miRNAs, miRs) are small non-coding RNA (ncRNA) molecules capable of regulating post-transcriptional gene expression. Imbalances in the miRNA network have been associated with the development of many pathological conditions and diseases, including cancer. Recently, miRNAs have also been linked to the phenomenon of multidrug resistance (MDR). MiR-7 is one of the extensively studied miRNAs and its role in cancer progression and MDR modulation has been highlighted. MiR-7 is engaged in multiple cellular pathways and acts as a tumor suppressor in the majority of human neoplasia. Its depletion limits the effectiveness of anti-cancer therapies, while its restoration sensitizes cells to the administered drugs. Therefore, miR-7 might be considered as a potential adjuvant agent, which can increase the efficiency of standard chemotherapeutics.